Nosocomial Infections: A Long-Lasting Challenge in Public Health - Shakti Rath1 , Naushaba Akhtar2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Nosocomial or hospital-borne infections are one of the most difficult challenges faced by health careprofessionals, as these infections are arises in hospital settings. Both human and non-human contaminationsare responsible for these infections inpatients during their hospital stay. This article helps to understand theepidemiology of nosocomial infections and to overcome major public health challenges. It also identifies thefactors responsible and the mode of transmission of these infections to overcome some major public healthchallenges.